Planetary Analog Field Operations as a Learning Tool - Groemer, Gernot; Ozdemir, Seda (Frontiers in Astronomy and Space Sciences, 2020)
Mars and Moon analog field missions are established tools to investigate the potential of instruments, workflows, materials and human factors for characterizing the astrobiological potential and geoscientific context of planetary surfaces. Historically, there is a broad spectrum on both the scientific focus and the performance parameters for analog missions. This applies specifically where mission performance parameters of a coordinated deployment of mission assets (e.g. rovers, human crewmembers or scientific instruments) is studied. We argue that scientific priorities and workflows shall be consolidated at an early planning stage of deep space missions while they can still impact the mission architecture design process. It is to be expected that a human-robotic mission to Mars or the Moon will include multiple field assets such as human explorers, robotic vehicles including aerial reconnaissance, mobility assets, habitat modules, stationary instruments and engineering elements for power, communication and in-situ resource utilization. These require more complex asset coordination compared to single-rover planetary rover missions. Therefore, we advocate an “Exploration Cascade” which helps to manage these multiple assets to optimize the scientific return of planetary surface missions, to search for extinct and-/or for extant traces of life and to characterize the geoscientific context of the sites of interest.